2021
DOI: 10.1108/bpmj-09-2020-0419
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perceived organizational support and green transformational leadership on sustainable organizational performance: a SEM approach

Abstract: PurposeThe study aims to scrutinize the concomitant associations between corporate social responsibility (CSR), perceived organizational support (POS), green transformational leadership (GTL) and organizational performance (OP). This paper aims to explore the role of intervening variable to measure the strength on the relationship between CSR and OP.Design/methodology/approachThis research administered a survey through self-administered questionnaire among the staff-level employees of construction companies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 62 publications
(76 reference statements)
3
35
0
Order By: Relevance
“…The empirical study by Zhao and Huang (2022) also indicates a positive relationship between GTL and sustainable business performance and claims that the firm has a high level of sustainable business performance, as it provides followers with green awareness and capabilities. Kusi et al (2021) reported that corporate social responsibility would lead to a higher level of organizational performance if GTL is encouraged in the firm. With its environmental orientation, GTL can promote the resources and capabilities required for green practice and bring sustainable economic and environmental performance and eventually improve a firm’s CA (Zameer et al , 2020; Zehir and Ozgul, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The empirical study by Zhao and Huang (2022) also indicates a positive relationship between GTL and sustainable business performance and claims that the firm has a high level of sustainable business performance, as it provides followers with green awareness and capabilities. Kusi et al (2021) reported that corporate social responsibility would lead to a higher level of organizational performance if GTL is encouraged in the firm. With its environmental orientation, GTL can promote the resources and capabilities required for green practice and bring sustainable economic and environmental performance and eventually improve a firm’s CA (Zameer et al , 2020; Zehir and Ozgul, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Influential transformational leaders supposedly articulate a shared vision of their firm's future and motivate organisational members to respond to the changing environment (Podsakoff et al, 1990). The transformational leader guides employees by instilling confidence and encouragement to adapt to changes that may offer value (Kusi et al, 2021). This confidence and motivation engage employees in innovative thinking, new working patterns and identifying new market opportunities, which are the fundamentals of SE.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…In normal conditions, the role of governments is to serve the needs of their subjects, to manage and regulate their productivity and to enhance their living standards to the benefit of the masses. Corporations are mainly firms owned by individuals in constant search of new opportunities and higher profit margins (Kusi et al , 2021). The collaboration between both parties is normal because both of them are considered to be part of the same system one is public, and the other one is private.…”
Section: Theoretical Frameworkmentioning
confidence: 99%